Geochemical characteristics of agricultural soils, Assiut governorate, Egypt - E. A. Abou El-Anwar (Bulletin of the National Research Centre, 2019)
Abstract Background The geochemical investigation of agricultural soil is a great demand because of its help in the characterization of soil and its suitability for cultivation. The urbanization, cultivation, and industrial activities at Assiut Governorate have adversely impacted the chemical composition of soil, especially its content of heavy metals. The study area includes El-Madabgh sewage station and many big industries; cement, fertilizers, and pharmaceutical. Results The Nile Valley soils are very comparable in composition and composed mainly of SiO2, Al2O3, Fe2O3, CaO, MgO, and TiO2 which represent about 88% of its chemical composition. The chemical composition gave an indication about the mineralogical assemblage of soil; quartz, clay minerals, and calcite. The results pointed to the mixed source (geogenic and anthropogenic) of Fe, Co, Cu, Ni, Zn, Zr, and Cr and the anthropogenic source of As, Pb, and Cd (especially phosphatic fertilizers) in the studied soil. Conclusion The studied soil chemistry affected mainly by the agricultural practices (application of fertilizers, pesticides, manure, and wastewater irrigation), industrial inputs, and atmospheric deposition. Generally, the Egyptian soil needs more geochemical studies to monitor its quality and enhance of its productivity.